Patterns of Reproductive Health and Sexuality Learning among Private High School Students at Yayasan Perguruan Mayjend Sutoyo in Medan - Siboro, Ayulina; Zuska, Fikarwin; Ginting, Bengkel; Ismail, Rizabuana; Sitorus, Henry (Universitas Medan Area, 2024)
The surge in premarital sexual incidents among teenagers leading to early marriages, prompted by unintended pregnancies, pervasive dating behavior beyond ethical boundaries, exposure to explicit content, and the prevalence of sexual diseases, underscores the critical need for comprehensive sexual and reproductive health education. This study explores the patterns and strategies employed in imparting sexual education and managing reproductive health among students at Yayasan Perguruan Mayjend Sutoyo High School, Sisingamangaraja Street, Medan. Employing qualitative methods, data was gathered through in-depth interviews and focus group discussions with students, Biology teachers, the School Principal, parents, and other stakeholders. The findings reveal that sexual education primarily stems from Biology teachers, who employ tactful language to teach human anatomy, reproductive organs, and sexual functions, adhering to contextual norms. Reproductive health education addresses the dynamics and consequences of casual sexual relationships, utilizing age-appropriate teaching materials. Teenagers seek diverse knowledge from parents, school descriptions, and online resources to navigate sexual and reproductive health challenges. However, the discreet provision of sexual education is influenced by traditional cultural values, fostering silence and shame, particularly in discussing male and female genitalia.